ДИАЛОГЪТ ГУНДРУМ - ВАЗОВ. ИЗДАТЕЛСКИ (РЕ)КОНСТРУКЦИИ - Димитрова, Малина (Bulgarian Language & Literature / Bulgarski Ezik i Literatura, 2021)
About Ivan Vazov everything seems to have been researched, written and published. Among the many literary criticisms devoted to his life and work, as well as documentary publications, the relationships with his translators and foreign publishers, to whom I believe we have a cultural and moral duty, are very rarely mentioned. However, the correspondence between him and the Croat Fran Gundrum-Oriovac stands out among all. No one else has translated as many of Vazov's works as this Croatian writer. Unfortunately, the acquaintance with Fran Gundrum's archive is indirect, but I would venture to focus on his translation practice, the regulation of relations between the two, their long-term cooperation and the reception of Vazov's work in Croatia. The proposed interpretation of the "File" does not claim to exhaust the relationship between the two. Our task is based on the personal correspondence published in Volume 10 of the Bulletin of the Institute of Literature of the Bulgarian Academy of Sciences in 1961 between Dr. Fran Gundrum and Ivan Vazov - to try to reconstruct the translation and publishing strategies of Fran Gundrum.